Impact of Netball Players of Indian Physical College Through Weight Jacket Training Programme - Kumar, Ravi; Singh, Sikander (International Journal of Psychosocial Rehabilitation, 2024)
In recent years and years, sports have improved dramatically in quality all across the world.The popularity of sports is currently growing at a rapid rate, and this happy trend is likely tocontinue in the future. The purpose of the study was to see how weight jacketing affected Vo2Max in high school football players. Thirty netball players from diverse assets, LNUPEGwalior, were chosen as subjects to obtain this inspiration driving the assessment. Thesubjects were developed between the ages of 19 and 24. They were split into two groups offifteen: Group I received weight-lifting training, while Group II functioned as a controlgroup that did not get any extra training outside of their regular games and practices. Priorto any training period, the participants were given the opportunity to try out a specified rulevariable, such as Vo2 max. The treadmill was used to find a specific worldview variable,such as Vo2 max. On the selected premise variable, the analysis of covariance (ANCOVA)was used to see if there were any significant differences between the test and controlassemblies. The centrality was tested with a 0.05 component of conviction, which wasdeemed appropriate. The current investigation demonstrated that there was a fundamentalqualification on Vo2 max among the exploratory and control groups